Team work and job satisfaction in nursing professionals at Ventanilla Hospital - Romani Larrea, Sergio Alfredo (2018)
The present research had relevance because the management interventions can favor both variables and consequently the patients. The objective of this research was to relate teamwork and job satisfaction in nurses at the Ventanilla hospital. The qualitative research, non-experimental and descriptive-correlational design were used. The sample consisted of 71 nurses, non-probabilistic sampling was used. The technique used was the survey with a questionnaire that had two parts: Perception of teamwork and job satisfaction, with 16 questions each. The data were analyzed with descriptive statistics and inferential analysis. The results indicate that the perception of teamwork (82%) and job satisfaction (90%) are in the middle level. A significant association of both variables was found in the Chi square tests (p = 0.000) and Spearman correlation (Rho = 0.45). The correlation is significant in the indicators of commitment (0.53), coordination (0.53), integration (0.33), equilibrium (0.33) and agreement (0.36). It is concluded that teamwork and job satisfaction have a significant association and mainly the indicators of commitment and coordination.